Implementation Model of Love Languages in Shaping Students' Character Through Islamic Religious Education at Mis Amal Bhakti Langkat - Wahidah Wahidah; Akrim Akrim (Dinasti International Journal of Education Management And Social Science, 2024)
The Prophet Muhammad (peace be upon him) was sent to perfect moral character. Religious education serves as the foundational basis for forming commendable character, beginning within the family environment that influences the growth and development of children from an early age. Globalization and technological advancements have impacted children's behavior, including the use of coarse and impolite language. This research aims to analyze the implementation of the language of love model in shaping students' character through Islamic religious education at MIS Amal Bhakti Langkat. This qualitative research uses a case study approach. Data collection techniques were conducted using survey methods. The data analysis technique used is descriptive statistics. The findings of the study indicate that the implementation of the language of love in shaping students' character has a positive impact, particularly in the responsive reactions of the students and helping them develop positively despite challenges from unsupportive family and environmental backgrounds.